Early Childhood Outdoor Learning Assessment Instrument - Yudha, Rivo Panji; Aini, Nur (JURNAL INDRIA (Jurnal Ilmiah Pendidikan Prasekolah dan Sekolah Awal), 2025)
This study focuses on the development of outdoor learning assessment instruments at RA Hafniratunnisa Namlea, which aims to assess early childhood development in the context of outdoor learning. This study uses a development model based on the approach (Define, Design, Develop, Disseminate) and involves assessment experts for instrument validation. The main focus of this research is on the development of comprehensive and functional instruments, not on the outdoor learning method or strategy itself. The resulting assessment instrument is designed to assess cognitive development, creativity, and other aspects of children's development through learning activities while playing in nature. This study also considers the limitations of the problem to maintain focus and get more targeted results. The instruments developed are required to be easy to understand by early childhood and relevant to creativity learning outcomes. The final result of this study is a valid assessment instrument that can be used by educators to assess children's development in the context of outdoor learning. These instruments include instructions for use, sub-instruments for each aspect of development, observation sheets and field notes, and interview sheets. Instrument validation is carried out through expert analysis and limited trials to several early childhood education institutions in certain regions. The conclusions drawn from this study show that the assessment instruments developed have been validated by experts and are suitable to be used to assess the development of children aged 5-6 years in the context of outdoor learning. This instrument is required to be in accordance with the learning objectives and use language that is easy for children to understand.